Demystifying modelling methods for trade policy - Piermartini, Roberta (WTO GenevaCH, 2005)
Focuses on two classes of quantitative tools-computable general equilibrium (CGE) models and gravity models. Offers a non-technical explanation of CGE and gravity models to trade policy makers.